The VEPP-5 injection complex modulator revision and operational experience - Akimov, A.V.; Bak, P.A.; Gusev, E.A.; Kazarezov, I.V.; Kot, N.H.; Chupyra, A.G.; Petrov, S.P.; Yudin, V.D. (Вопросы атомной науки и техники, 2004)
For the VEPP-5 injection complex klystrons (5045, SLAC Lab., USA) power supply the four modulators producing a pulse voltage of 23.5 kV, a current of 6.3 kA, a pulse-top-duration of 3.7 µs are used. The modulator scheme designed over ten years ago has proved its reliability and let us to find out and study the weak spots of the modulators. The output voltage stability and pulse-to-pulse time jitter improvements are made. The results of the thyratrons TGI1-2500/50 and TGI1-5000/50A long-term exploitation in the VEPP-5 injection complex modulators are presented. The test results of the thyratron TGI1-2500/50 operating in the mode of more then twice pulse current overload at the nominal mode of modulator operation are also presented.